THE INVESTIGATION OF THE EFFECT OF AXIAL FORCE ON DEFORMATION OF A BENT TUBE - Hassan, Hassan Raheem (Antis-Publisher, 2026)
Objective: The inquiry may yield evidence regarding the impact of tension force on the displacement of the neutral axis, strain, and wall thickness in rotary draw bending. Method: The finite element analysis use the ABAQUS software to evaluate the non-linear response of structures. Results: The simulation results align closely with the experimental findings, and we also compared the effects of rotary draw bending with and without axial force, as discussed in previous work without axial force. Novelty: The tube diameter, wall thickness, bending radius, material characteristics, and bending angle are the primary parameters influencing the change of neutral axis shifting and the tensile force in the tube. The neutral axis at the center of the tube shifts to the inner arc due to the additional axial force.